Baseline CD4 count and the time interval between the initial HIV infection and diagnosis among PLHIV in Bhutan - Lekey khandu (Immunity, Inflammation and Disease, 2021)
Abstract Introduction CD4 count is an important predictor of disease progression, opportunities infection, deaths, and to understand the time interval between initial HIV infection to the first diagnosis. However, baseline CD4 count and the time period between initial infection and the diagnosis amongst PLHIV in Bhutan never been evaluated. Methods This is a retrospective study of the diagnosed PLHIV from the existing data system from January 10 to 30, 2021. Out of 512 reported HIV cases, 488 of those who were more than or equal to 18 years old and had their CD4 count testing within 6 months before initiating ART were considered for analysis. Descriptive statistical analysis was used to analyze the characteristics of the study population and relationship were established using the χ 2 Test. We have sought ethics approval and waiver for informed consent as it is the retrospective study of the client's record. The client's confidentiality was ensured by removing all the identifiers. Results The mean CD4 was 345 cells/ml for males and females. Twenty‐five percent of the clients had CD4 counts below 200, 30%, between 200 and 349, 25% between 350 and 499, and 20% above 500 cells/ml. A larger number of males showed a CD4 count below 200 cells/ml while more females showed a CD4 count more than 500 cells/ml. The mean time interval between initial infection to the first diagnosis was 4 years in males and females. However, about one‐fourth were found to have been infected between 5 and 8 years before diagnosis and less than 10% were diagnosed within less than 1 year of infection. Conclusions The study revealed a late diagnosis of HIV infection in Bhutan thereby risking the transmission to the community and risk of severe disease and mortality. The upscaling of voluntary counseling and testing, medical screening, and alternative methods like community‐based testing including HIV Self Testing for early detection needs to be implemented in the country.